Primitive "Spindle Cell Variant" (Sarcomatoid Variant) Diffuse Large B-Cell Lymphoma of the Uterine Cervix: Description and Outcome of a Rare Case. (November 2016) - Fratoni, Stefano; Abruzzese, Elisabetta; Trawinska, Malgorzata M.; Niscola, Pasquale; de Fabritiis, Paolo; Santeusanio, Giuseppe
Abstract : A very rare case of primary diffuse large B-cell lymphoma of the uterine cervix characterized by "spindle cell variant" morphology ("sarcomatoid subtype") is described along with a discussion of the challenging diagnosis due to its rarity and presenting clinical and pathological features.